Association between Polymorphism rs1799732 of DRD2 Dopamine Receptor Gene and Personality Traits among MMA Athletes - Marta Niewczas (Genes, 2021)
Four factors—namely, harm avoidance, novelty seeking, reward addiction and persistence—represent the nature of temperament that is not genetically determined in itself. It was shown in earlier studies that a strong propensity to look for novelty or a tendency to engage in risky behavior is correlated with genetic variants in the area of the genes encoding dopamine receptors. Therefore, the aim of this study is to determine whether there is a relationship between personality traits and genetic variants in the area of the DRD2 dopamine receptor gene in MMA athletes. The participants consisted of 85 mixed martial arts (MMA) athletes and 284 healthy, non-MMA male participants. Their personality traits were measured using the Revised Temperament and Character Inventory. Blood was collected for genetic assays and all samples were genotyped using the real-time PCR method. We observed a statistically significant effect of a complex factor of the DRD2 rs1799732 genotype on MMA participants’ control and reward dependence. Engaging in high-risk sport may be associated with several personality characteristics. The DRD2 rs1799732 polymorphism may be associated with reduced harm avoidance in martial arts athletes, thereby modulating athletes’ predisposition to participate in high-risk sport.